A Balanced Heuristic Mechanism for Multirobot Task Allocation of Intelligent Warehouses. (10th November 2014) - Zhou, Luowei; Shi, Yuanyuan; Wang, Jiangliu; Yang, Pei
Abstract : This paper presents a new mechanism for the multirobot task allocation problem in intelligent warehouses, where a team of mobile robots are expected to efficiently transport a number of given objects. We model the system with unknown task cost and the objective is twofold, that is, equally allocating the workload as well as minimizing the travel cost. A balanced heuristic mechanism (BHM) is proposed to achieve this goal. We raised two improved task allocation methods by applying this mechanism to the auction and clustering strategies, respectively. The results of simulated experiments demonstrate the success of the proposed approach regarding increasing the utilization of the robots as well as the efficiency of the whole warehouse system (by 5~15%). In addition, the influence of the coefficient α in the BHM is well-studied. Typically, this coefficient is set between 0.7~0.9 to achieve good system performance.